2004
DOI: 10.1182/blood-2004-01-0046
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of all-trans-retinoic acid treatment reveals systematic posttranscriptional control mechanisms in acute promyelocytic leukemia

Abstract: All-trans-retinoic acid (ATRA) induces growth inhibition, differentiation, and apoptosis in cancer cells, including acute promyelocytic leukemia (APL). In APL, expression of promyelocytic leukemia protein retinoic acid receptor-␣ (PML-RAR␣) fusion protein, owing to the t(15; 17) reciprocal translocation, leads to a block in the promyelocytic stage of differentiation. Here, we studied molecular mechanisms involved in ATRA-induced growth inhibition and myeloid cell differentiation in APL. By employing comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 76 publications
(73 reference statements)
4
96
2
Order By: Relevance
“…This disease leads to the accumulation of pathological hematopoietic precursors in bone marrow. In this study, Harris et al [169] showed that all-trans-retinoic acid treatment of acute promyelocytic leukemia cells resulted in resetting the regulation of the posttranscriptional suppressive pathways. Fifty-nine differentially expressed proteins were pointed out, including eukaryotic initiation and elongation factors, heterogeneous nuclear ribonucleoproteins (RNPs), and small nuclear RNPs [169].…”
Section: Leukemia and Lymphomamentioning
confidence: 80%
See 1 more Smart Citation
“…This disease leads to the accumulation of pathological hematopoietic precursors in bone marrow. In this study, Harris et al [169] showed that all-trans-retinoic acid treatment of acute promyelocytic leukemia cells resulted in resetting the regulation of the posttranscriptional suppressive pathways. Fifty-nine differentially expressed proteins were pointed out, including eukaryotic initiation and elongation factors, heterogeneous nuclear ribonucleoproteins (RNPs), and small nuclear RNPs [169].…”
Section: Leukemia and Lymphomamentioning
confidence: 80%
“…In this study, Harris et al [169] showed that all-trans-retinoic acid treatment of acute promyelocytic leukemia cells resulted in resetting the regulation of the posttranscriptional suppressive pathways. Fifty-nine differentially expressed proteins were pointed out, including eukaryotic initiation and elongation factors, heterogeneous nuclear ribonucleoproteins (RNPs), and small nuclear RNPs [169]. The response to p38 mitogen-activated protein kinase inhibitor SB203580 was evaluated in transformed follicular lymphoma cells by quantitative proteomic (ICAT-LC-MS/MS) and transcriptional (cDNA microarrays) analyses by Lin et al [170].…”
Section: Leukemia and Lymphomamentioning
confidence: 80%
“…Among these, the initiation factor IF-2, the elongation factors eEF-1gamma and eEF-1alpha1, the heterogeneous nuclear ribonucleoprotein hnRNP F, and the eukaryotic initiation factors eIF4A-1 and eIF4A-2 are known to be down-regulated by ATRA in acute promyelocytic cells. [27][28][29] In particular, IF-2, eEF-1gamma and eEF-1alpha1 have roles in the elongation stages of the protein synthesis mechanism, and hnRNP F, eIF4A-1 and eIF4A-2 have roles in mRNA processing and transport. This may suggest that ATRA-induced differentiation of NB could share these six effectors with ATRA-induced differentiation in PML cells.…”
Section: J Journal Of Proteome Researchmentioning
confidence: 99%
“…Previously, 2D-PAGE analyses of protein changes were performed to study chemoresistance, 22 to search for markers for tumor diagnosis in NB cell lines, 23,24 and to study quantitatively and qualitatively differences in healthy and pathological NB mouse samples. 25,26 Moreover, proteomic characterization of differentiation induced by ATRA has been described in promyelocytic cells 7,27,28 and in mouse embryonic stem cells. 29 However, very little is known about the large-scale protein components of early stage differentiation of NB cell lines into neural cells by ATRA.…”
Section: Introductionmentioning
confidence: 99%
“…[68][69][70] In that way, in a recent study, 71 the protein profile of the AML subtypes has been analyzed, in an attempt to delineate the aberrant gene expression underlying the pathogenesis of this malignancy. The proteomic analysis, performed in blast from newly diagnosed acute myeloid leukemia patients, allowed to the identification of several proteins differentially expressed in the leukemia subtypes.…”
Section: Role Of Tissue Factor In Hematological Malignanciesmentioning
confidence: 99%